Interventions to reduce perceived stress among university students in LMICs: a scoping review - Mangozho, Tinashe Nigel (Department of Psychiatry and Mental Health, 2026)
Stress has been defined as the perception that one's resources to meet a demand for change are not adequate. It is also an emotional response to stressors. Stressors and cumulative adversities have been associated with mental health problems. Research suggests that university students are a vulnerable part of the population with exposure to diverse stressors and a high prevalence of mental health problems, including psychological distress, depression, and anxiety. This may be due to experiencing several stressors and decreased access to protective factors, such as family support. Although studies have explored the effectiveness of interventions to prevent stress related problems among university students, most studies originate from high income settings and primarily focus on studies from these settings. As a result, a synthesis of the current body of evidence regarding interventions to reduce stress in university students focused on low- and middle-income settings, is warranted. Method; This review used the Arksey & O'Malley (2005) scoping review framework that includes six stages: (1) identification of the research question, (2) identification of relevant studies, (3) selection of studies, (4) charting the data, (5) collating, summarising and (6) collaboration. The following databases were used for the identification of relevant studies: Google Scholar, Academic Search Premier, Africa-Wide Information, CINAHL, ERIC, Health Source: Nursing/Academic Edition, MEDLINE, APA PsycInfo, PubMed, and Scopus. Abstracts of relevant studies were screened before the final articles were selected for inclusion in the review. Eligible studies were reviewed using the CASP checklist. Reporting of methods follows the Preferred Reporting Items for Systematic Reviews and Meta Analyses – Extension for Scoping Reviews (PRISMA-ScR). Data was collected using post-hoc tool designed for this review by the first author. The data extracted included bibliographic information, country of origin, type of study, study population, methodology, interventions, outcome measurement and key findings relating to the review question. Results This study identified eight studies. Six were randomised control trials and two were quasi experimental studies using a pre-test post-test design. Seven studies were from lower-middle income countries and one from an upper middle-income country investigating the 13 effectiveness of a range of interventions including: Mindfulness Based Interventions (n = 2),Rational Emotive Therapies (n = 3), Cognitive Behavioural Therapies (n = 1), Breathing Therapy and Emotional Freedom Therapies (n = 1), and Critical Thinking Interventions (n = 1). Primary outcome measures focussed on a stressed related variable were all self-report including the Depression, Anxiety and Stress Scale (DASS) (n = 2); the Perceived Stress Scale (PSS) (n = 4); the Exam Stress Scale (ExamSS) (n = 1); and the ASQ (n = 1). Only one study used a validated tool provided in the study participants' first language. Appraisal for this study was done using the CASP Appraisal tool (see Appendix 6). Four papers were rated as high quality (scoring highly in all three domains on the CASP) and 4 were rated as medium (scoring highly in at least 2 of the three domains of the CASP). The results of the analysis showed significant reductions in stress-related problems which were maintained at follow-up. Although all studies provided significant results for the chosen intervention, they were plagued by several limitations. Conclusion; This scoping review set out to identify interventions to reduce stress in university students in LMIC. The results of this scoping review suggested that there is not enough evidence to make definitive statements on the effectiveness of interventions to reduce perceived stress. The findings highlight the significant limitations of available studies and the need for further research in this area.